2010
DOI: 10.1103/physrevb.81.041406
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic layer-by-layer growth of graphene on vicinal SiC(0001) surfaces

Abstract: Epitaxial graphene is formed on vicinal SiC͑0001͒ surfaces via high temperature annealing in vacuum. Steps act as a significant "kicker" of graphene nucleation to feed C atoms. At elevated temperatures, graphene growth is controlled by the decomposition of Si-C bonds at step edges, Si desorption, and C diffusion on the surface. The limited Si desorption is due to the dependence of the growth rate on the thickness of graphene layers. The fabricated graphene layer͑s͒ acts as a Si-diffusion barrier, which in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 23 publications
2
82
0
Order By: Relevance
“…Older graphene sheets are lift up by the formation of the new graphene sheet, and the oldest graphene sheet remains on the topmost. This mechanism is consistent with the experimental observations [75,76]. The experiment further revealed that this mechanism is also applicable to the C-face as well as the Si-face [76].…”
Section: Discussion On Quasi-stable Buffer Layer Structuresupporting
confidence: 80%
“…Older graphene sheets are lift up by the formation of the new graphene sheet, and the oldest graphene sheet remains on the topmost. This mechanism is consistent with the experimental observations [75,76]. The experiment further revealed that this mechanism is also applicable to the C-face as well as the Si-face [76].…”
Section: Discussion On Quasi-stable Buffer Layer Structuresupporting
confidence: 80%
“…[28][29][30][31][32][33] In standard processes, vicinal SiC surfaces are gas etched in the H 2 atmosphere. Depending on the duration of this stage, the partial erosion of the material at the steps occurs which may lead to the formation of macrosteps 28,29 or a significant modification of the step shapes. 30 Typically, prepared SiC samples are annealed in a neutral atmosphere at a very high temperature which leads to graphitization that begins at the steps.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, graphene can be prepared by different methods such as mechanical cleavage or exfoliation [2], chemical reduction of graphite oxide [3], epitaxial growth by SiC thermal graphitization in vacuum [4] or in an Ar atmosphere [5] and chemical vapour deposition (CVD) on transition metals [6]. Very promising is the synthesis of graphene on SiC substrates at a relatively low temperature [7] based on the carbon segregation from a metal layer saturated by carbon.…”
Section: Introductionmentioning
confidence: 99%